Patient specific total temporomandibular joint reconstruction: A review of biomaterial, designs, fabrication and outcomes - Divya Mehrotra; Sumit Kumar; Pankhuri Mehrotra; Richa Khanna; Vikram Khanna; Dominic Eggbeer; Peter Evans (Elsevier, 2021)
Purpose: The aim of this article was to systematically review the available literature on patient specific total temporomandibular joint total joint replacement (PS-TMJR) implants for their biomaterial, designs, fabrication techniques and their outcomes. Methods: A literature review was conducted using PubMed, and science direct databases using the key words three-dimensional printing, 3D printing, CAD CAM, computer aided designing, computer aided manufacturing, additive technology, custom made implants, patient specific implants in combination with Temporomandibular joint, TMJ surgery. Results: The search revealed 2760 articles, of which 374 were in English and discussed TMJ reconstruction. Further filtering shortlisted 74 articles that discussed PS-TMJR. Duplicates were removed and additional added from article references. 39 articles describing biomaterial, designing and fabrication of PS-TMJR implants and their outcomes were selected for analysis. Conclusions: Although PS-TMJR implants allow a better anatomical fit, improved fixation, and safeguard various structures such as the inferior alveolar nerve, they vary in designs, material and fabrication techniques. However, PS-TMJR printed with SLM and EBM technologies have yet to be compared with the conventional ones in terms of mechanical strength, and clinical outcome. With emerging bioprinting technologies, even newer biomaterials should be considered for 3D printing of PS-TMJR devices designed to achieve harmony in function between the joint device, bone and masticatory muscles.